The use of teledentistry and Artificial Intelligence (AI) in dental and oral health services for the elderly in the era of the covid-19 pandemic: A systematic review - Bahruddin Thalib; Rifaat Nurrahma; Asmawati; Alqarama M. Thalib; Mohammad NF. Taufik (DiscoverSys Inc., 2022)
Objective: This paper aims to determine the use of teledentistry and AI in the elderly to maintain the health of their oral cavity and teeth during the COVID-19 pandemic. Methods: Technology in dentistry today is developing very rapidly, improving the quality of dental and oral health services. During the pandemic, the elderly has concerns about Covid-19 contamination when they have to see a dentist. Their situation has led to discussions and efforts to use teledentistry and Artificial intelligence to facilitate services and care for the elderly during the pandemic. Results: Teledentistry is used as a medium for consultation, diagnosis, referral system, treatment, and follow-up. While Artificial Intelligence (AI) has been used in diagnostic, patient data management, restoration, and CAD/CAM-based denture manufacture, detecting periodontal disease, and dental radiology. Conclusion: Teledentistry and AI can be a promising alternative in dental and oral health services to reduce anxiety and fear of contamination with Covid-19. The technologies make it easier for health workers, especially dentists, to maintain and improve the quality of life of the elderly during the pandemic.